The Analysis of Metaphorical Expression in Billie Eilish’s Songs - Tegar Arif Topan (Jurnal Sosial Humaniora dan Pendidikan, 2025)
A metaphor is a kind of figurative language. Songwriters use metaphors to facilitate listeners' comprehension of song lyrics' meanings. The objective of this study was to examine the kinds, meanings, and functions of metaphors in three chosen songs by Billie Eilish. The study was conducted using a descriptive qualitative technique. The study methodology was executed in three phases: data gathering techniques, data analysis techniques, and presentation strategies for the analysis outcomes. Data collection was conducted via non-participant methods and note-taking approaches. This study analyzes the lyrics of three selected Billie Eilish songs: "Wildflower," "What I Was Made For," and "Blue." The study identified four categories of metaphors in Billie Eilish's songs: animal metaphors, anthropomorphic metaphors, concrete-to-abstract metaphors, and synesthetic metaphors. The metaphorical use of Billie Eilish's song encompasses informational, emotive, and directive roles. The findings indicate that Billie Eilish's songs often serve as a medium to advocate for issues faced by women, including insecurity, envy, and romantic dilemmas.